[Basis for bases ; Filipino value ; Joey Ayala [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
A look at the U.S. bases issue in light of the visit of U.S. Secretary of Defense Richard Cheney; value conflicts in Filipinos; and interview with Joey Ayala as poet, singer and songwriter.